L'artisanat de l'os à l'époque Gallo-Romaine : de l'ostéologie à l'archéologie expérimentale - Barbier, Marc, (Archaeopress Roman archaeology ;, 2016)
The transfer, in 1981, of the town museum collections in Sens (Yonne) to the old Archbishop's palace required great discretion and an underground passage was planned between the two buildings. Preventive archaeological excavations unearthed 22 Gallo-Roman bone combs, as well as a further 17 pieces when the excavation area was expanded. This exceptional concentration of bone artefacts incited the author to start on an experimental search at a time when bone artefacts were not finding much interest among specialists. However, it was extremely adventurous to piece together a bone-worker production line and create a never before archaeologically discovered appliance used in Roman times. Obviously, the first reproductions have been directed towards combs. This title presents an analysis of the 22 Gallo-Roman bone combs.